2020
DOI: 10.3390/ma13030510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Gaseous Environment on the Electrical Conductivity of Multi-Walled Carbon Nanotube Films over a Wide Temperature Range

Abstract: The surrounding gas atmosphere can have a significant influence on the electrical properties of multi-walled carbon nanotube (CNT) ensembles. In this study, we subjected CNT films to various gaseous environments or vacuum to observe how such factors alter the electrical resistance of networks at high temperatures. We showed that the removal of adsorbed water and other contaminants from the surface under reduced pressure significantly affects the electrical conductivity of the material. We also demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The temperature cycling tests that we have performed here do not quantify such long-term degradation that occurs when the sensors are exposed to ambient gases. It is worthwhile to mention in this context that a recent study has pointed out that the electrical conductivity of the CNTs is hardly affected by the presence of different gases of inert or oxidizing character across a large temperature range (25 to 300 °C) and only the presence of hydrogen as ambient gas has some effect on altering the electrical conductivity of the CNTs across this temperature range . On the other hand, GOs or r-GOs (reduced graphene oxides) are known for their interactions with various gases and, accordingly, they are often used for sensing of these gases. , Therefore, it is highly possible that the GO of the CNT-GO sensors will interact with the ambient gases, which in turn might lead to a long-term degradation of these CNT-GO sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature cycling tests that we have performed here do not quantify such long-term degradation that occurs when the sensors are exposed to ambient gases. It is worthwhile to mention in this context that a recent study has pointed out that the electrical conductivity of the CNTs is hardly affected by the presence of different gases of inert or oxidizing character across a large temperature range (25 to 300 °C) and only the presence of hydrogen as ambient gas has some effect on altering the electrical conductivity of the CNTs across this temperature range . On the other hand, GOs or r-GOs (reduced graphene oxides) are known for their interactions with various gases and, accordingly, they are often used for sensing of these gases. , Therefore, it is highly possible that the GO of the CNT-GO sensors will interact with the ambient gases, which in turn might lead to a long-term degradation of these CNT-GO sensors.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The structural characteristics and concentration of carbon species produced during an FC-CVD reaction are strongly related to gas chemistry and its composition. 24,25 Researchers have commonly used inert carrier gases such as nitrogen, [26][27][28] argon, [29][30][31] and helium 32,33 and reducing gases such as hydrogen 13,34,35 and ammonia 36 for the synthesis of CNT. It has been observed that the gaseous composition affects the morphology, structure, and nanotube aerial density of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this relation, they can be used as sensors to monitor the external environment. Firstly, it was demonstrated that the surrounding gas atmosphere can greatly impact the electrical properties of CNT networks [ 1 ]. The electrical conductivity of CNT films was changed when the material was exposed to vacuum or a selection of gases such as methane, ethylene, oxygen, ammonia, nitrogen, argon, and hydrogen.…”
mentioning
confidence: 99%